Dimethyl 4-(3,4-dimethoxyphenyl)-2,6-dimethyl-1,4-dihydropyridine-3,5-dicarboxylate - Shahani, Tara (International Union of Crystallography, 2010)
In the title compound, C(19)H(23)NO(6), the 1,4-dihydropyridine ring is twisted slightly from planarity, with a maximum deviation of 0.101 (1) Å, and adopts a very flattened boat conformation. The dihedral angle formed between the plane through the four C atoms of the 1,4-dihydropyridine ring and the benzene ring is 84.67 (7)°. In the crystal structure, intermolecular N—H⋯O and C—H⋯O hydrogen bonds link the molecules into a three-dimensional network.